Un indicateur global d’évaluation de la vulnérabilité écologique du milieu le long de grandes infrastructures linéaires : Pourquoi ? Comment ? - Émilie Lorant-Plantier (Cybergeo, 2014)
According to the legislation, natural habitat and biodiversity has to be considered for main linear infrastructure projects. Nevertheless, this requirement is often difficult to fulfill due to the inherent characteristics of these projects and the lack of efficient tools to evaluate ecological vulnerability. Based on a database setup and a dedicated monitoring index development for the areas affected by the Seine-North Europe project, this study puts forward a process which could reduce its deficiency.